(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
A characteristic feature of the modern era is the decrease in physical activity of the younger generation due to the massive development of computer technology, high physical and mental workload in educational institutions, as well as the lack of prestige of a healthy lifestyle. The use of modern health-improving motor systems will allow students to form the need for regular classes in types of motor activity.